Determinación de macronutrientes en los sedimentos de estanques acuícolas como fertilizantes orgánicos agrícolas en Iquitos – 2022 - Carrión Bardales, Paulo Alberto (2023)
The objective of the research work was to determine macronutrients in the sediments of aquaculture ponds of fish farms in Iquitos-2022 that can be used as organic agricultural fertilizers. The present quantitative research is of a comparative descriptive type, the study population considered all the aquaculture ponds of the fish farms located in the Iquitos-Nauta road axis. The sample was selected according to the convenience criteria of the researcher, three ponds were chosen that contained fish of the gamitana variety in the harvesting stage: the sample size was 3000 grams for each pond. To determine the physical characteristics and chemical composition in content of macronutrients for agricultural use, three samples from different ponds were used, obtaining average values of the physical properties (pH): Agricultural sediments pH: 7.40; 6.68 and 6.82 (ponds 1, 2 and 3), Commercial fertilizers pH: 6.8 - 7.2 (FERTILAB, LOMBEC, estrucplan and compostaindustrial), chemical composition ponds: Protein:1.35%; Phosphorus: 2.8%; Potassium: 3.6%; Calcium: 51.20%; Magnesium:7.12%, commercial fertilizers composition: Nitrogen: 2.60; 2.31; 2.0 Phosphorus: 8.0; 1.46; 2.5 and 0.4 Potassium: 2.50; 2.37; 1.50 Calcium: 8.0; 9.70;2.50 and 0.4 Magnesium: 2.50; 1.42; 0.4 (FERTILAB, LOMBEC, estrucplan and compostaindustrial respectively). A comparative analysis between the two shows that the values are similar in some major components and lower in others. It can be concluded that aquaculture pond sediments can be used as agricultural fertilizers for various forest species.